Izbira jezika v računalniškem izrazju - Oter Gorenčič, Mija (Slavistična revija, 2002)
The paper analyzes the state of Slovene computer terminology and its development in the last ten years, as is evident from the selected and representative material. The article also presents all the institutions concerned with Slovene computer terminology and creating Slovene computer terminological system. The paper also point out the problem of variants in computer terminology.
Keywords: computer science; računalništvo; Slovene; slovenščina; strokovni jezik; terminologija; terminology